Pathophysiology of penetrating captive-bolt stunning of horses - Katharine A Fletcher; Beatrice Benedetti; Georgina Limon; Andrew Grist; Barbara Padalino; Mariano Hernández-Gil; Troy J Gibson (Animal Welfare, 2025)
There has been limited research into the effectiveness of penetrating captive bolt (PCB) for stunning horses (Equus caballus) at slaughter. This study observed 100 horses at a commercial abattoir in Mexico, stunned using pneumatic PCB. Animals were assessed at the time of stunning and immediately after for signs of effective/ineffective stunning and shot positioning, with macroscopic gross brain pathology conducted to determine brain trauma. Twenty-five percent (25/100) received more than one shot and 28% (28/100) displayed behavioural signs of ineffective stunning. Of these 28 animals, all had deviations of more than 10 mm from the suggested shot position outlined by the Humane Slaughter Association with rostral-caudal deviation associated with an absence of damage to the thalamus, midbrain, and pons. Forty-four percent (44/100) of animals displayed no damage to critical brain structures (thalamus, midbrain, pons and medulla), with this associated with ineffective stunning. Overall, 16% of shots missed the brain (16/100), with a higher proportion of poll shots (30%) missing the brain compared to frontal shots (12%). There is the potential, when animals are shot into the poll, for paralysis from damage to the spinal cord and caudal brainstem structures. Appropriate position, angle and performance of PCB is therefore vital to achieving an effective stun, by targeting critical brain structures responsible for maintaining consciousness and ensuring proper PCB maintenance. Animals should be routinely checked between stunning and exsanguination, with minimal time between these stages, to minimise recovery of consciousness and alleviate suffering for horses at slaughter.